2020
DOI: 10.3390/su12145647
|View full text |Cite
|
Sign up to set email alerts
|

International Entrepreneurial Orientation and the Intention to Internationalize

Abstract: This paper presents a conceptual model of international entrepreneurial intention (IEI) through the lens of planned behavior and expectancy-valence theories. Extending the entrepreneurial intentions literature, where attitude to sustainability has started to have an increasingly important influence, to post-launch decisions, we provide an improved theoretical rationale for new venture internationalization, clarify the relationship between entrepreneurial orientation (EO) and IEI, and more closely align the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 154 publications
0
12
0
Order By: Relevance
“…The concept of IEO stems from the entrepreneurship literature-most notably Miller's (1983) and Covin and Slevin's (1989) works-which form the fundamental base for much research. The general tendency in the related literature is to focus upon the original underlying concepts of risk-taking, proactiveness, and innovation and to evaluate firms operating in an international context upon such measures (Covin & Miller, 2014;McDougall-Covin et al, 2014;Ruzzier et al, 2020;Tayauva, 2011;Zhang et al, 2012). Another approach significantly modifies the three indicated elements of the EO concept, by describing IEO as "a combination of innovative, proactive and risk-seeking behaviour that crosses national borders, and is intended to create value in organizations" (McDougall & Oviatt, 2000, p. 903).…”
Section: Theoretical Background: Ieomentioning
confidence: 99%
“…The concept of IEO stems from the entrepreneurship literature-most notably Miller's (1983) and Covin and Slevin's (1989) works-which form the fundamental base for much research. The general tendency in the related literature is to focus upon the original underlying concepts of risk-taking, proactiveness, and innovation and to evaluate firms operating in an international context upon such measures (Covin & Miller, 2014;McDougall-Covin et al, 2014;Ruzzier et al, 2020;Tayauva, 2011;Zhang et al, 2012). Another approach significantly modifies the three indicated elements of the EO concept, by describing IEO as "a combination of innovative, proactive and risk-seeking behaviour that crosses national borders, and is intended to create value in organizations" (McDougall & Oviatt, 2000, p. 903).…”
Section: Theoretical Background: Ieomentioning
confidence: 99%
“…It has been shown that entrepreneurship in a specific region is relatively stable due to the temporal stability of certain variables (e.g., culture) [15][16][17]. Thus, it has been suggested that entrepreneurship in a regional context can be self-reinforcing [18][19][20]. There are two lines of research about the variables that favor entrepreneurship in a regional context [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…TPB is widely used to predict individuals' behavioral intentions and explain the entrepreneurial process (Munir, Jiangfei and Ramzan 2019). The key relationships studied is the link between values, underlying attitudes, and how they drive intentions and, subsequently, behaviors (Ruzzier, Douglas, Ruzzier and Hojnik 2020). Some recent studies have attempted to apply the TPB to explain entrepreneurial intentions and actions (Kautonen, Gelderen andFink 2015, Obschonka, Silbereisen, Canter andGoethner 2015).…”
Section: Theory Of Planned Behavior and Hypotheses Developmentmentioning
confidence: 99%